Pengaruh Metode Eja dalam Meningkatkan Kemampuan Membaca Permulaan Pada Siswa Kelas Rendah - Azizah Cahyatul; Restika Sari; Tika Dwi Astari (Pusat Riset dan Inovasi Nasional, 2024)
You really need to pay attention to beginning reading because if basic learning is not strong or solid, it will cause difficulties when reading properly. This article describes the results of using the spelling method in improving beginning reading skills in lower grade students. This research uses qualitative research methods obtained from literature studies. According to several literature and research conducted regarding the use of spelling methods, there has been an increase in students' initial reading abilities, especially in lower grades. The use of the spelling method can be said to be very successful in improving students' initial reading abilities.